Examination rules and student effort - Jochen Michaelis; Benjamin Schwanebeck (Philipps-University Marburg, School of Business and Economics, 2016)
This paper contributes to the economics of examination rules. We show how rational students reallocate their learning effort as a response to a charge for the second exam attempt, a cap on the maximum resit mark, an adjustment of the passing standard, a variation of the time span between two attempts, a minimum requirement to qualify for the second attempt, and a malus points account. The effort maximizing rule is the malus account, a charge for the second attempt delivers the highest overall passing probability.
Keywords: I21; I23; D81; 330; student performance; resits; examination rules; standard setting; higher education